Recent advances in the application of MXenes for neural tissue engineering and regeneration - Menghui Liao; Qingyue Cui; Yangnan Hu; Jiayue Xing; Danqi Wu; Shasha Zheng; Yu Zhao; Yafeng Yu; Jingwu Sun; Renjie Chai (Neural Regeneration Research, 2024)
Transition metal carbides and nitrides (MXenes) are crystal nanomaterials with a number of surface functional groups such as fluorine, hydroxyl, and oxygen, which can be used as carriers for proteins and drugs. MXenes have excellent biocompatibility, electrical conductivity, surface hydrophilicity, mechanical properties and easy surface modification. However, at present, the stability of most MXenes needs to be improved, and more synthesis methods need to be explored. MXenes are good substrates for nerve cell regeneration and nerve reconstruction, which have broad application prospects in the repair of nervous system injury. Regarding the application of MXenes in neuroscience, mainly at the cellular level, the long-term in vivo biosafety and effects also need to be further explored. This review focuses on the progress of using MXenes in nerve regeneration over the last few years; discussing preparation of MXenes and their biocompatibility with different cells as well as the regulation by MXenes of nerve cell regeneration in two-dimensional and three-dimensional environments in vitro. MXenes have great potential in regulating the proliferation, differentiation, and maturation of nerve cells and in promoting regeneration and recovery after nerve injury. In addition, this review also presents the main challenges during optimization processes, such as the preparation of stable MXenes and long-term in vivo biosafety, and further discusses future directions in neural tissue engineering.